2019
DOI: 10.3390/jcm8081183
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TP53 and PIK3CA Mutations in Circulating Tumor DNA Using Next-Generation Sequencing in the Screening Process for Early Breast Cancer Diagnosis

Abstract: Circulating tumor DNA (ctDNA) has emerged as a non-invasive “liquid biopsy” for early breast cancer diagnosis. We evaluated the suitability of ctDNA analysis in the diagnosis of early breast cancer after mammography findings, comparing PIK3CA and TP53 mutations between tumor biopsies and pre-biopsy circulating DNA. Matched plasma and frozen fresh tissue biopsies from patients with Breast Imaging-Reporting and Data System (BIRADS) 4c/5 mammography findings and subsequent diagnosis of primary breast cancer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 43 publications
(48 reference statements)
1
29
0
Order By: Relevance
“…Later, another meta-analysis was able to demonstrate the diagnostic utility of TP53 mutations in cfDNA for advanced breast cancer with a diagnostic performance of 0.94 [ 43 ]. Frequencies of TP53 mutation reported in these studies agree with some recent ones reporting frequencies of 34% in tissue [ 44 , 45 ] and of 31% [ 46 ] and 32.5% [ 47 ] in plasma of primary breast cancer patients. Nevertheless, mutation frequency is higher in some other studies, showing a TP53 mutation prevalence of 41% [ 45 ], 50% [ 7 ] and 51.7% [ 24 ].…”
Section: Variability Of Tp53 Status Between Liquid and Solid Biopssupporting
confidence: 92%
See 2 more Smart Citations
“…Later, another meta-analysis was able to demonstrate the diagnostic utility of TP53 mutations in cfDNA for advanced breast cancer with a diagnostic performance of 0.94 [ 43 ]. Frequencies of TP53 mutation reported in these studies agree with some recent ones reporting frequencies of 34% in tissue [ 44 , 45 ] and of 31% [ 46 ] and 32.5% [ 47 ] in plasma of primary breast cancer patients. Nevertheless, mutation frequency is higher in some other studies, showing a TP53 mutation prevalence of 41% [ 45 ], 50% [ 7 ] and 51.7% [ 24 ].…”
Section: Variability Of Tp53 Status Between Liquid and Solid Biopssupporting
confidence: 92%
“…Of note, the region of study for a particular gene is also of great importance. Most early studies only analyzed TP53 mutations in exons 4 and 8, comprising the majority of the known mutations [ 92 ] and later sequencing studies of the whole gene revealed lower concordances between liquid and solid biopsies, possibly due to the fact that rare mutations might be present at extremely low VAFs to be detected in both specimens [ 44 ]. In addition, genetic alterations such as methylation may also impact on TP53 gene expression without the need for identifying point mutations [ 93 ], thus inclusion of further biomarkers in both solid and liquid biopsies might improve their diagnostic and prognostic utility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the ctDNA concentration in patients with BRAF-mutated urothelial carcinoma is increased compared to that in wild-type patients, demonstrating that the BRAF mutation in urothelial carcinoma may be detectable in the plasma of these canines. CtDNAs with mutations in several genes have been detected in human patients with cancer, and ctDNA analysis provides critical clinical information to improve diagnosis in these patients [6,7,17].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Jimenez-Rodriguez et al. [30] compared the mutational profiles of solid tumours and plasma samples from early breast cancer patients using the amplicon-based SafeSEQ (Sysmex Inostics) technology and a fixed-gene panel for plasma sequencing. Interestingly, the authors observed that plasma DNA sequencing permitted the identification of clonal mutations not detected in tumour biopsy sequencing.…”
Section: Circulating-tumour Dna In Early Breast Cancermentioning
confidence: 99%